Efforts to Increase Teachers' Competence of E-Learning in the Covid-19 Era - Iswadi; Herinto Sidik Iriansyah (Yayasan Almubarak Fil Ilmi, 2021)
This study aims to improve the ability of teachers in online learning in the Covid-19 era (Case study on teachers of SMP Negeri 3 MuaraTiga). The subjects in this study were all teachers at SMP Negeri 3 MuaraTiga, totaling 38 teachers. Based on observations, these teachers were not maximal in implementing online learning. The research instrument is in the form of a questionnaire sheet, which is useful for recording all events in the implementation of teacher assignments in online learning during the study. The results showed that in Cycle I, the understanding of teachers in online learning carried out during the learning process at SMP Negeri 3 MuaraTiga was 1,269. The average value is 36.8, with a percentage of 76.30%. Thus the understanding of the teachers at SMP Negeri 3 MuaraTiga is in the Good Enough category. Then it increased after the implementation of Cycle II of Online Learning which was carried out during the learning process at SMP Negeri 3 MuaraTiga, the number was 1,341. The average value is 38, with a percentage of 81.16%. Thus the understanding of the teachers at SMP Negeri 3 MuaraTiga is in the Good category. The results showed that the teacher's understanding of online learning at SMP Negeri 3 MuaraTiga was in the good category.